The Optimal Taxation of International Investment Income: Reply - Horst, Thomas (Quarterly Journal of Economics, 1982)
Journal Article The Optimal Taxation of International Investment Income: Reply Get access Thomas Horst Thomas Horst Taxecon Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 97, Issue 2, May 1982, Page 381, https://doi.org/10.2307/1880766 Published: 01 May 1982